Cognitive fatigue from schema rigidity and entropy externalization: a free energy principle perspective - Ezzedini, Souhir (Frontiers in Psychology, 2026)
Cognitive fatigue is typically described as a psychobiological state that arises from intensive and/or prolonged cognitive performance and is experienced as a subjective feeling of exhaustion and lack of energy. It has been predominantly explained through models focused on internal resource depletion or diminished attention. Yet, such perspectives overlook the systemic and dynamic interplay between the brain and the environment. This article introduces a novel theoretical framework grounded in Friston's Free Energy Principle and informed by thermodynamic intuitions about open systems, conceptualizing cognitive fatigue as an outcome of the interaction between cognitive schema rigidity, increasing entropy, and imbalances between internal processes and external environmental demands. Cognitive schemas, which serve as stabilizing mental structures, play a key role in reducing uncertainty, maintaining cognitive stability, and supporting coherent perception–action. When their rigidity—rooted in cognitive inertia—limits their capacity to adapt to environmental changes, it hinders the brain's ability to externalize entropy. This results in an accumulation of unresolved internal disorder and heightened cognitive load, progressively exacerbating fatigue. This theoretical framework emphasizes the importance of brain-environment interactions in mitigating entropy accumulation and highlights the need for greater focus on schema flexibility to enhance cognitive adaptability. By integrating systemic and dynamic perspectives, this framework provides new insights into the mechanisms of cognitive fatigue and its implications for performance in demanding contexts.